Reactivity of cardiorespiratory system in bronchial asthma patients according to the tests with respiratory maneuvers performance - O. P. Romanchuk; V. I. Velychko; Ya. I. Bazhora (Zaporožskij Medicinskij Žurnal)
Today asthma is defined as allergic inflammation of the respiratory tract, which is associated with hyperreactivity of the bronchi to various stimuli. The basis of asthma clinical picture forms broncho-obstructive syndrome, which is polymorphic in the mechanism of formation, and this determines the heterogeneity of asthma pathogenesis. Due to the anatomical and functional relationship with the cardiovascular system, this mechanism should be considered in a complex manner studying the composition changes in the associated cardiopulmonary system.